Norovirus Capsid Protein-Derived Nanoparticles and Polymers as Versatile Platforms for Antigen Presentation and Vaccine Development - Ming Tan; Xi Jiang (MDPI AG, 2019)
Major viral structural proteins interact homotypically and/or heterotypically, self-assembling into polyvalent viral capsids that usually elicit strong host immune responses. By taking advantage of such intrinsic features of norovirus capsids, two subviral nanoparticles, 60-valent S60 and 24-valent P24 nanoparticles, as well as various polymers, have been generated through bioengineering norovirus capsid shell (S) and protruding (P) domains, respectively. These nanoparticles and polymers are easily produced, highly stable, and extremely immunogenic, making them ideal vaccine candidates against noroviruses. In addition, they serve as multifunctional platforms to display foreign antigens, self-assembling into chimeric nanoparticles or polymers as vaccines against different pathogens and illnesses. Several chimeric S60 and P24 nanoparticles, as well as P domain-derived polymers, carrying different foreign antigens, have been created and demonstrated to be promising vaccine candidates against corresponding pathogens in preclinical animal studies, warranting their further development into useful vaccines.